NUEVA LOCALIDAD GEOGRAFICA PARA BERBERIS NEGERIANA TISCHLER (BERBERIDACEAE) EN LA PROVINCIA DE ARAUCO, REGION DEL BIO BIO - Gómez, Persy; Belov, Michail; San Martín, José (Gayana Botánica, 2008)
This note reports the finding of a population of Berberis negeriana Tischler (Berberidaceae), in the province of Arauco, Bio Bio Region (37°42’17" S y 73°19’43" W) in the center south of Chile. The population was found between Nothofagus obliqua and species of the Valdiviano Forest.